High-temperature-resistant cement strength stabilizing material, application thereof and oil well cementing cement slurry system
Composite materials with different activities were prepared through multi-stage calcination of kaolin, which solved the problem of strength decline of the cement ring of the oil well under high temperature environment, and achieved the long-term strength maintenance of cement stone at high temperature.
Patent Information
- Application Number
- CN202311383747.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively suppress the strength decline of the cement ring of the oil well under high temperature environments, resulting in failure of the wellbore seal integrity.
Using composite materials of kaolin, first calcined kaolin and second calcined kaolin, kaolin products with different structures and activities are prepared through different calcining temperatures and times, and act on the early, middle and late stages of cement hydration, thereby improving the overall strength of cement stone.
This material can maintain the long-term strength of cement stone without decline at high temperatures of 180-250℃, and is suitable for high-temperature well sealing needs such as deep, ultra-deep, extra-deep and dry hot rocks.
Smart Images

Figure BDA0004510381880000131
Abstract
Description
Technical Field
[0001] The invention relates to the field of oil and gas well cementing, and in particular to a high temperature resistant cement strength stabilizing material and its application in inhibiting oil well cement strength decay and an oil well cementing cement slurry system. Background Art
[0002] The integrity of cement ring seal is an important part of wellbore integrity and the premise and foundation for the safe and efficient development of oil and gas resources. As my country's oil and gas resource exploration continues to develop in the direction of unconventional, deep, ultra-deep and ultra-deep layers, more and more complex formations are encountered, and the formation temperature and pressure are getting higher and higher. High temperature has brought great challenges to the integrity of wellbore seals.
[0003] The silicate cement sheath is a brittle material and is not resistant to high temperatures. When the temperature reaches 110-120°C, its strength will decrease. The strength decay can usually be suppressed by adding quartz sand. On the one hand, although quartz sand is a volcanic ash material, it does not have hydraulic properties. After adding it, it will reduce the initial strength of the cement sheath / cement stone, and the higher the amount added, the lower the strength. On the other hand, as the temperature rises (over 180°C), the inhibitory effect of quartz sand on the strength decay of the cement sheath at high temperatures is greatly weakened. As time goes by, the internal structure and bonding surface of the cement sheath continue to deteriorate, and the porosity and permeability increase, resulting in failure of the wellbore sealing integrity.
[0004] Therefore, there is an urgent need for a material that can inhibit the strength decline of cement paste and is suitable for high-temperature environments of deep, ultra-deep, extra-deep, hot dry rock and other oil and gas well formations. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem that the existing technology of oil well cement high temperature strength decay resistant materials still has poor inhibitory effect on cement sheath strength decay under high temperature, and to provide a cement strength stabilizing material and its application and an oil well cementing cement slurry system, wherein the cement strength stabilizing material can improve the early strength, mid-term strength and late strength of cement stone.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a cement strength stabilizing material, wherein the cement strength stabilizing material comprises kaolin, a first calcined kaolin and a second calcined kaolin; wherein,
[0007] In the cement strength stabilizing material, the weight ratio of the kaolin, the first calcined kaolin and the second calcined kaolin is (2-6): (1-5): (2-6);
[0008] The first calcined kaolin is obtained by first calcining kaolin, and the temperature of the first calcination is 650-850° C.;
[0009] The second calcined kaolin is obtained by subjecting kaolin to a second calcination, and the temperature of the second calcination is 1050-1350°C.
[0010] The second aspect of the present invention provides an oil well cementing slurry system, wherein the slurry system comprises: oil well cement and the cement strength stabilizing material provided by the present invention; wherein,
[0011] Based on 100 parts by weight of the oil well cement, the weight content of the cement strength stabilizing material in the cement slurry system is 40-100 parts.
[0012] A third aspect of the present invention provides an application of the cement strength stabilizing material provided by the present invention in inhibiting the decline of oil well cement strength.
[0013] Through the above technical solution, the beneficial effects of the present invention are:
[0014] The kaolin, the first calcined kaolin and the second calcined kaolin in the high-temperature resistant cement strength stabilizing material of the present invention have different activities and can act on the early, middle and late stages of cement hydration, thereby maintaining the high early strength of the cement stone and the continuous and stable growth of the strength, and can maintain the long-term strength of the cement stone at a high temperature of 180-250°C without decay, and is suitable for high-temperature environments of deep, ultra-deep, extra-deep, hot dry rock and other oil and gas well formations.
[0015] The high temperature resistant cement strength stabilizing material of the present invention does not need to be compounded with quartz sand, and can inhibit the early and long-term strength decline of cement paste when used alone, thereby eliminating the adverse effects of quartz sand on the early strength, pore throat structure and cement slurry stability of cement paste.
[0016] The preparation method of the high temperature resistant cement strength stabilizing material of the present invention is simple, and does not require operations such as hydrothermal reaction and acid-base modification, and can be directly mixed and stirred after high temperature calcination. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a cement strength stabilizing material, wherein the cement strength stabilizing material comprises kaolin, a first calcined kaolin and a second calcined kaolin; wherein,
[0019] In the cement strength stabilizing material, the weight ratio of the kaolin, the first calcined kaolin and the second calcined kaolin is (2-6): (1-5): (2-6);
[0020] The first calcined kaolin is obtained by first calcining kaolin, and the temperature of the first calcination is 650-850° C.;
[0021] The second calcined kaolin is obtained by subjecting kaolin to a second calcination, and the temperature of the second calcination is 1050-1350°C.
[0022] Calcination of kaolin will change the structure of kaolin, thereby changing the activity of kaolin. Calcining kaolin at different temperatures can obtain calcined products with different structures and activities, which can act on different stages of cement hydration to improve the strength of cement paste at different stages. Compounding kaolin with first calcined kaolin and second calcined kaolin obtained by calcining at different temperatures can improve the early strength, mid-term strength and late strength of cement paste.
[0023] According to the present invention, preferably, the first calcination comprises maintaining the temperature at 650-850° C. for more than 1 hour.
[0024] The present invention has no particular limitation on the duration of the first calcination, as long as the reaction is sufficient to fully transform the structure and activity of the kaolin after the first calcination. Preferably, the duration of the first calcination is greater than or equal to 1 hour. In order to reduce energy consumption while ensuring sufficient calcination, the duration of the first calcination is more preferably 1-4 hours.
[0025] According to the present invention, preferably, the second calcination comprises maintaining the temperature at 1050-1350° C. for more than 1 hour.
[0026] The present invention has no particular limitation on the duration of the second calcination, as long as the reaction is sufficient to fully transform the structure and activity of the kaolin after the second calcination. Preferably, the duration of the second calcination is greater than or equal to 1 hour. In order to reduce energy consumption while ensuring sufficient calcination, the duration of the second calcination is more preferably 1-4 hours.
[0027] The first calcined kaolin obtained by calcining kaolin at a temperature of 650-850℃ for more than 1h is mainly amorphous non-crystalline structure with high activity, which mainly acts in the early stage of cement hydration and is used to improve the early strength of cement paste. The second calcined kaolin obtained by calcining kaolin at a temperature of 1050-1350℃ for more than 1h is a crystalline structure and a transition structure from amorphous to crystalline structure with low activity, which mainly acts in the middle and late stages of cement hydration and is used to improve the medium and long-term strength of cement paste. Kaolin mainly acts in the early and middle stages of cement hydration and is used to improve the early and medium-term strength of cement paste.
[0028] In order to further improve the ability of high temperature resistant cement strength stabilizing material to inhibit the decline of oil well cement strength, preferably, Al in the kaolin 2 O 3 The content of SiO is greater than or equal to 30wt%, preferably 35-45wt%; 2 The content is greater than or equal to 45%, preferably 50-60wt%.
[0029] The present invention has no particular limitation on the heating rates of the first calcination process and the second calcination process, as long as the temperature can be stably increased. Preferably, the first calcination further comprises: heating to a maintenance temperature (650-850°C) at a rate greater than or equal to 0.5°C / min.
[0030] Preferably, the second calcination further comprises: heating to a maintenance temperature (1050-1350° C.) at a rate greater than or equal to 0.5° C. / min.
[0031] According to the present invention, preferably, the average particle size of the kaolin is 30-70 μm, preferably 40-50 μm. When the average particle size of the kaolin meets this range, the high temperature resistant cement strength stabilizing material can have a good particle gradation with other solid particles in the cement slurry, thereby maintaining good slurry rheological properties and sedimentation stability, and having good hydration reaction activity.
[0032] After calcining kaolin for the first time and calcining for the second time respectively, kaolin, kaolin calcined for the first time and kaolin calcined for the second time are directly mixed to obtain a high temperature resistant cement strength stabilizing material. The present invention has no particular limitation on the mixing method, as long as the three can be mixed uniformly.
[0033] According to a specific embodiment of the present invention, the method for preparing the cement strength stabilizing material comprises the following steps:
[0034] S1. placing a first portion of kaolin in a calcining furnace, and performing a first calcination on the kaolin, wherein the first calcination comprises: heating to 650-850° C. at a rate of greater than or equal to 0.5° C. / min, and maintaining the temperature at 650-850° C. for more than 1 hour to obtain a first calcined kaolin;
[0035] S2, placing the second portion of kaolin in a calcining furnace, and performing a second calcination on the kaolin, wherein the second calcination comprises: heating to 1050-1350° C. at a rate of greater than or equal to 0.5° C. / min, and maintaining the temperature at 1050-1350° C. for more than 1 hour to obtain a second calcined kaolin;
[0036] S3. Put the third portion of kaolin, the first calcined kaolin and the second calcined kaolin in a weight ratio of (2-6): (1-5): (2-6) into a mixer and stir and mix until the mixture is uniform and no pseudo particles are observed by naked eye, thereby obtaining the cement strength stabilizing material.
[0037] The second aspect of the present invention provides an oil well cementing slurry system, wherein the slurry system comprises: oil well cement and the cement strength stabilizing material provided by the present invention; wherein,
[0038] Based on 100 parts by weight of the oil well cement, the weight content of the cement strength stabilizing material in the cement slurry system is 40-100 parts, preferably 50-80 parts.
[0039] According to the present invention, preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 4-10 parts by weight of a fluid loss additive.
[0040] The present invention does not particularly limit the type of fluid loss agent, and conventional fluid loss materials in the art can be selected and commercially available. Preferably, the fluid loss agent is selected from a copolymer comprising a structural unit from 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and a structural unit from acrylamide. The present invention does not particularly limit the weight average molecular weight of the copolymer, and the weight ratio of the structural unit from AMPS to the structural unit from acrylamide, as long as the performance as a fluid loss agent can be met. For example, a fluid loss agent with a brand name of SCF-J purchased from Texas Continental Shelf Petroleum Engineering Technology Co., Ltd. can be selected.
[0041] According to the present invention, preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 5-15 parts by weight of a retarder.
[0042] The present invention does not particularly limit the type of retarder, and conventional retarding materials in the art can be selected and commercially available. Preferably, the retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid multipolymer (AMPS multipolymer). The present invention does not particularly limit the weight average molecular weight of the AMPS multipolymer and the proportion of the structural units contained in the AMPS multipolymer, as long as the performance as a retarder can be satisfied. For example, a retarder with a brand name of SCR purchased from Texas Continental Shelf Petroleum Engineering Technology Co., Ltd. can be selected.
[0043] According to the present invention, preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 0.1-2 parts by weight of a defoamer.
[0044] The present invention does not particularly limit the type of defoaming agent, and conventional defoaming agents in the art can be selected and commercially available. Preferably, the defoaming agent is selected from silicone defoaming agents, for example, an organosilicon defoaming agent with a brand name of SCFD-2 purchased from Texas Continental Shelf Petroleum Engineering Technology Co., Ltd. can be selected.
[0045] According to the present invention, preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 30-100 parts by weight of water.
[0046] According to a more preferred embodiment of the present invention, the cement slurry system comprises, by weight, 100 parts of oil well cement, 40-100 parts of cement strength stabilizer, 4-10 parts of fluid loss reducer, 5-15 parts of retarder, 0.1-2 parts of defoamer and 30-100 parts of water. The content of each component in the cement slurry system meets this condition, which can further improve the slurry performance of the cement slurry system.
[0047] According to the present invention, preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises: less than 2 parts by weight of a dispersant, and / or less than 300 parts by weight of a density regulator, and / or less than 3 parts by weight of a suspension stabilizer.
[0048] When the density of the cement slurry system is lower than 1.85 g / cm 3 Or higher than 1.95g / cm 3 When adding 30-300 parts by weight of density regulator; optionally, adding suspension stabilizer, preferably, adding 0.3-3 parts by weight of suspension stabilizer to obtain a density lower than 1.85g / cm 3 Or higher than 1.95g / cm 3 In a preferred embodiment, in order to improve the fluidity of the cement slurry, 0.1-2 parts by weight of a dispersant is also added.
[0049] The present invention has no particular limitation on the type of dispersant, as long as it can meet the performance requirements of a dispersant, and can be commercially available. For example, a polycarboxylic acid dispersant and / or a ketone-aldehyde condensate dispersant can be selected, for example, a polycarboxylic acid dispersant purchased from Texas Continental Shelf with a brand name of SCD can be selected.
[0050] The present invention has no particular restrictions on the type of density regulator, as long as it can adjust the density of the cement slurry system, and can be commercially available. For example, one or more of slag, fly ash, glass beads, iron ore powder, iron powder, barite powder and manganese powder can be selected. The amount of density regulator added is adjusted according to the density of the cement slurry system.
[0051] The present invention has no particular limitation on the type of suspension stabilizer, as long as it can maintain the solid particles in the cement slurry system in suspension without precipitation, and can be commercially available. For example, a clay suspension stabilizer with a brand name of TAS153 purchased from Tianjin Baoen can be selected.
[0052] The third aspect of the present invention provides an application of the cement strength stabilizing material provided by the present invention in inhibiting the decline of cement strength in oil wells. In particular, the application under the condition of a temperature of 180-250°C. The high temperature resistant cement strength stabilizing material provided by the present invention can keep the long-term strength of cement stone at a high temperature of 180-250°C without decline, and is suitable for the sealing needs of high temperature wellbores such as deep, ultra-deep, extra-deep, and dry hot rocks.
[0053] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, all are conventional methods; the reagents and materials used, unless otherwise specified, can be obtained from commercial sources. The reagents and determination methods involved in the following examples and comparative examples are as follows:
[0054] The oil well cement was Grade G cement purchased from Jiahua Company.
[0055] Unless otherwise specified, the following examples and comparative examples all use Al 2 O 3 The content is 39wt%, SiO 2 The content is 54wt% kaolin.
[0056] Prepared according to GB / T 19139-2012 standard with a density of 1.90g / cm 3 Cement slurry.
[0057] The following preparation example is used to illustrate the preparation of high temperature resistant cement strength stabilizing material.
[0058] Preparation Example 1
[0059] S1, heating to 750°C at a rate of 6°C / min, maintaining kaolin with an average particle size of 50 μm at 750°C for 2 hours, performing a first calcination to obtain first calcined kaolin;
[0060] S2, raising the temperature to 1200° C. at a rate of 6° C. / min, maintaining the kaolin having an average particle size of 50 μm at 1200° C. for 2 h, and performing a second calcination to obtain a second calcined kaolin;
[0061] S3. Put kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin in a blender at a weight ratio of 30:40:30, and stir and mix them until they are evenly mixed and no agglomerated particles are observed with the naked eye, thereby obtaining high temperature resistant cement strength stabilizing material A1.
[0062] Preparation Example 2
[0063] The cement strength stabilizing material is prepared according to the method of Preparation Example 1, except that the weight ratios of kaolin, the first calcined kaolin and the second calcined kaolin are different. Specifically, in S3, "the kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin are placed in a mixer at a weight ratio of 40:30:30 for stirring and mixing" is used to replace "the kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin are placed in a mixer at a weight ratio of 30:40:30 for stirring and mixing". The high temperature resistant cement strength stabilizing material A2 is obtained.
[0064] Preparation Example 3
[0065] The cement strength stabilizing material is prepared according to the method of Preparation Example 2, except that the temperatures of the first calcination and the second calcination are different. Specifically, in S1, "the temperature is raised to 700°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm is maintained at 700°C for 2h, and the first calcination is carried out" is used to replace "the temperature is raised to 750°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm is maintained at 750°C for 2h, and the first calcination is carried out"; in S2, "the temperature is raised to 1100°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm is maintained at 1100°C for 2h, and the second calcination is carried out" is used to replace "the temperature is raised to 1200°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm is maintained at 1200°C for 2h, and the second calcination is carried out". High temperature resistant cement strength stabilizing material A3 is obtained.
[0066] Preparation Example 4
[0067] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that kaolin with different aluminum and silicon content was selected. Specifically, the kaolin in S1, S2 and S3 was selected from Al2 O 3 The content is 28wt%, SiO 2 The kaolin content is 62wt%. The high temperature resistant cement strength stabilized material A4 is obtained.
[0068] Preparation Example 5
[0069] S1, heating to 950°C at a rate of 6°C / min, maintaining kaolin with an average particle size of 50 μm at 950°C for 2 hours, and calcining to obtain calcined kaolin;
[0070] S2. Put kaolin with an average particle size of 50 μm and calcined kaolin in a mixer at a weight ratio of 40:60 and stir and mix until the mixture is uniform and no agglomerated particles are observed with the naked eye, thereby obtaining high temperature resistant cement strength stabilizing material A5.
[0071] Preparation Example 6
[0072] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the temperature of the second calcination was different. Specifically, in S2, "the temperature was raised to 1000°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm was maintained at 1000°C for 2h, and the second calcination was performed" was used to replace "the temperature was raised to 1200°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm was maintained at 1200°C for 2h, and the second calcination was performed". The high temperature resistant cement strength stabilizing material A6 was obtained.
[0073] Preparation Example 7
[0074] The cement strength stabilizing material is prepared according to the method of Preparation Example 2, except that the weight ratios of kaolin, the first calcined kaolin and the second calcined kaolin are different. Specifically, in S3, "the kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin are placed in a mixer at a weight ratio of 20:60:20 for stirring and mixing" is used to replace "the kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin are placed in a mixer at a weight ratio of 40:30:30 for stirring and mixing". The high temperature resistant cement strength stabilizing material A7 is obtained.
[0075] Preparation Example 8
[0076] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the temperature of the first calcination was different. Specifically, in S1, "the temperature was raised to 600°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm was maintained at 600°C for 2h, and the first calcination was performed" was used to replace "the temperature was raised to 750°C at a rate of 6°C / min, and kaolin with an average particle size of 50μm was maintained at 750°C for 2h, and the first calcination was performed". The high temperature resistant cement strength stabilizing material A8 was obtained.
[0077] The following examples are used to illustrate the preparation of oil well cementing slurry.
[0078] Examples 1-4
[0079] The high temperature resistant cement strength stabilizing materials A1-A4 are respectively prepared into cement slurries to obtain cement slurries P1-P4. The specific formulas are as follows:
[0080] The preparation density is 1.90g / cm 3 The cement slurry is composed of: by weight, 100 parts of cement, 60 parts of high temperature resistant cement strength stabilizing materials (A1-A4), 10 parts of retarder (AMPS multipolymer, SCR, purchased from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.), 8 parts of fluid loss reducer (AMPS and acrylamide copolymer, SCF-J, purchased from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.), 0.5 parts of defoamer (organic silicon, SCFD-2, purchased from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.), and 49 parts of clean water. Oil well cementing cement slurries P1-P4 were prepared.
[0081] Example 5
[0082] Oil well cementing slurry was prepared according to the formula of Example 2, except that the content of high temperature resistant cement strength stabilizing material in the cement slurry was different. Specifically, "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced by "40 parts of high temperature resistant cement strength stabilizing material A2", and "49 parts of clean water" was replaced by "41 parts of clean water". Oil well cementing slurry P5 was prepared.
[0083] Example 6
[0084] The oil well cementing slurry was prepared according to the formula of Example 2, except that the content of the high temperature resistant cement strength stabilizing material in the cement slurry was different. Specifically, "90 parts of the high temperature resistant cement strength stabilizing material A2" replaced "60 parts of the high temperature resistant cement strength stabilizing material A2", and "60 parts of clean water" replaced "49 parts of clean water". The oil well cementing slurry P6 was prepared.
[0085] Comparative Example 1
[0086] Oil well cementing slurry was prepared according to the formula of Example 2, except that "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced by "60 parts of quartz sand with an average particle size of 50 μm", and "49 parts of clean water" was replaced by "51 parts of clean water". Oil well cementing slurry D1 was prepared.
[0087] Comparative Example 2
[0088] The oil well cementing slurry was prepared according to the formula of Example 2, except that the cement slurry formula did not contain high temperature resistant cement strength stabilizing material to obtain the oil well cementing slurry D2.
[0089] Comparative Example 3
[0090] The oil well cementing slurry was prepared according to the formula of Example 2, except that the first calcined kaolin was used to replace the second calcined kaolin of equal weight in the high temperature resistant cement strength stabilizing material. That is, in S3, "the kaolin with an average particle size of 50 μm and the first calcined kaolin were put into a mixer at a weight ratio of 40:60 for stirring and mixing" was used to replace "the kaolin with an average particle size of 50 μm, the first calcined kaolin and the second calcined kaolin were put into a mixer at a weight ratio of 40:30:30 for stirring and mixing". The oil well cementing slurry D3 was prepared.
[0091] Comparative Example 4
[0092] Oil well cementing slurry was prepared according to the formula of Example 2, except that "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced with "60 parts of high temperature resistant cement strength stabilizing material A5", to obtain oil well cementing slurry D4.
[0093] Comparative Example 5
[0094] Oil well cementing slurry was prepared according to the formula of Example 2, except that "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced with "60 parts of high temperature resistant cement strength stabilizing material A6". Oil well cementing slurry D5 was obtained.
[0095] Comparative Example 6
[0096] Oil well cementing slurry was prepared according to the formula of Example 2, except that "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced with "60 parts of high temperature resistant cement strength stabilizing material A7", to obtain oil well cementing slurry D6.
[0097] Comparative Example 7
[0098] The oil well cementing slurry was prepared according to the formula of Example 2, except that the content of the high temperature resistant cement strength stabilizing material in the cement slurry was different. Specifically, "60 parts of the high temperature resistant cement strength stabilizing material A2" was replaced by "30 parts of the high temperature resistant cement strength stabilizing material A2", and "49 parts of clean water" was replaced by "37 parts of clean water". The oil well cementing slurry D7 was prepared.
[0099] Comparative Example 8
[0100] Oil well cementing slurry was prepared according to the formula of Example 2, except that "60 parts of high temperature resistant cement strength stabilizing material A2" was replaced with "60 parts of high temperature resistant cement strength stabilizing material A8", to obtain oil well cementing slurry D8.
[0101] Test Case
[0102] The cement slurries prepared in the embodiments and comparative examples were cured at a temperature of 250° C. and a pressure of 21 MPa. The compressive strength of the cement pastes at different curing ages was tested according to the method specified in GB / T 19139-2012. The results are shown in Table 1.
[0103] Table 1
[0104]
[0105] It can be seen from the results in Table 1 that the early strength of cement stone after high-temperature curing of cement slurries prepared in Examples 1-6 is relatively high, and the strength continues to grow steadily. Comparative Example 1 uses quartz sand as cement strength stabilizing material, while Comparative Example 2 does not use cement strength stabilizing material, and the cement strength stabilizing material used in Comparative Example 3 does not use second calcined kaolin. The cement strength stabilizing material used in Comparative Example 4 uses calcined kaolin outside the first and second calcination temperature ranges, and the cement strength stabilizing material used in Comparative Example 5 reduces the temperature of the second calcination. The cement strength stabilizing material used in Comparative Example 6 changes the weight ratio of kaolin, first calcined kaolin, and second calcined kaolin. Comparative Example 7 reduces the amount of high-temperature resistant cement strength stabilizing material in the cement slurry. After high-temperature curing of cement slurries prepared in Comparative Examples 1-7, the cement stone all has a medium- and long-term strength decline. The cement strength stabilizing material used in Comparative Example 8 reduces the temperature of the first calcination, and the early strength of the cement stone prepared in the cement slurry is significantly reduced after high-temperature curing. This shows that adding the high temperature resistant cement strength stabilizing material of the present invention to cement slurry in a suitable proportion can maintain the high early strength of cement paste and the continuous and stable growth of strength, and can maintain the long-term strength of cement paste at a high temperature of 250°C without decay.
[0106] In addition, Example 4 uses different kaolins to prepare cement strength stabilizing materials, and Examples 5 and 6 respectively reduce and increase the amount of high temperature resistant cement strength stabilizing materials in cement slurry. Compared with Example 2, although the long-term strength of cement stone after high temperature curing at 250°C of the cement slurry prepared in Examples 4, 5 and 6 does not decline, the early strength is reduced. This shows that when kaolin with aluminum and silicon elements meeting the preferred conditions is selected to prepare cement strength stabilizing materials, and when the amount of high temperature resistant cement strength stabilizing materials added to cement slurry meets the preferred conditions, the early strength of cement stone after high temperature curing of the prepared cement slurry can be further improved.
[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cement strength stabilizing material, characterized in that: The cement strength stabilizing material comprises kaolin, first calcined kaolin and second calcined kaolin; wherein, In the cement strength stabilizing material, the weight ratio of the kaolin, the first calcined kaolin and the second calcined kaolin is (2-6): (1-5): (2-6); The first calcined kaolin is obtained by first calcining kaolin, and the temperature of the first calcination is 650-850° C.; The second calcined kaolin is obtained by subjecting kaolin to a second calcination, and the temperature of the second calcination is 1050-1350°C.
2. The cement strength stabilizing material according to claim 1, characterized in that: The first calcination includes maintaining the temperature at 650-850° C. for more than 1 hour.
3. The cement strength stabilizing material according to claim 1 or 2, characterized in that: The second calcination comprises maintaining the temperature at 1050-1350° C. for more than 1 hour.
4. The cement strength stabilizing material according to any one of claims 1 to 3, characterized in that: The content of Al2O3 in the kaolin is greater than or equal to 30wt%, preferably 35-45wt%; the content of SiO2 is greater than or equal to 45%, preferably 50-60wt%.
5. The cement strength stabilizing material according to claim 2, characterized in that: The first calcination further comprises: heating to a maintenance temperature at a rate greater than or equal to 0.5° C. / min.
6. The cement strength stabilizing material according to claim 3, characterized in that: The second calcination further comprises: heating to a maintenance temperature at a rate greater than or equal to 0.5° C. / min.
7. The cement strength stabilizing material according to any one of claims 1 to 6, characterized in that: The average particle size of the kaolin is 30-70 μm, preferably 40-50 μm.
8. An oil well cementing slurry system, characterized in that: The cement slurry system comprises: oil well cement and the cement strength stabilizing material according to any one of claims 1 to 8; wherein: Based on 100 parts by weight of the oil well cement, the weight content of the cement strength stabilizing material in the cement slurry system is 40-100 parts, preferably 50-80 parts.
9. The cement slurry system according to claim 8, characterized in that: Based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 4-10 parts by weight of a fluid loss reducer; Preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 5-15 parts by weight of a retarder; Preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises 0.1-2 parts by weight of a defoamer; Preferably, the cement slurry system further comprises 30-100 parts by weight of water; Preferably, based on 100 parts by weight of the oil well cement, the cement slurry system further comprises: less than 2 parts by weight of a dispersant, and / or less than 300 parts by weight of a density regulator, and / or less than 3 parts by weight of a suspension stabilizer.
10. Use of the cement strength stabilizing material according to any one of claims 1 to 7 in inhibiting the decline of oil well cement strength, preferably at a temperature of 180-250°C.